Oxidative Stress and Antioxidants in Chronic Rhinosinusitis with Nasal Polyps - Junhu Tai; Jae-Min Shin; Jaehyung Park; Munsoo Han; Tae Hoon Kim (MDPI AG, 2023)
Oxidative stress results from an imbalance between the production of reactive oxygen species and the body's antioxidant defense system. It plays an important role in the regulation of the immune response and can be a pathogenic factor in various diseases. Chronic rhinosinusitis (CRS) is a complex and heterogeneous disease with various phenotypes and endotypes. Recently, an increasing number of studies have proposed that oxidative stress (caused by both environmental and intrinsic stimuli) plays an important role in the pathogenesis and persistence of CRS. This has attracted the attention of several researchers. The relationship between the presence of reactive oxygen species composed of free radicals and nasal polyp pathology is a key topic receiving attention. This article reviews the role of oxidative stress in respiratory diseases, particularly CRS, and introduces potential therapeutic antioxidants that may offer targeted treatment for CRS.